PENGARUH PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BALAI PERLINDUNGAN TANAMAN PANGAN DAN HORTIKULTURA PROVINSI KALIMANTAN TENGAH - Erika Nadeak, Tio; Syamsudin, Achmad; Harjoni, Harjoni; Ruzaini Abdi, Muhammad (Penerbit Lafadz Jaya, 2025)
The Food Crops and Horticulture Protection Agency of Central Kalimantan Province plays an important role in maintaining the productivity of food crops and horticulture in the in the Central Kalimantan Province. This study aims to determine the influence of career development and work discipline on employee loyalty, with job satisfaction as an intervening variable. The research employs a quantitative-associative approach using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) with the help of Smart Pls 3.0. Data were collected using a Likert-scale questionnaire distributed to 38 38 civil servants of the Central Kalimantan BPTPH. The results show that career development and work discipline have a significant and significant impact on employee loyalty. Both variables also increase job satisfaction, which then acts as a link in relation to employee loyalty. These findings emphasize that to increase employee loyalty, the Central Kalimantan BPTPH needs not only to strengthen career development policies and enforce work discipline, but also to prioritize efforts to increase employee job satisfaction, which is a key mechanism in building long-term commitment and loyalty.